2014
DOI: 10.1039/c3ta15304e
|View full text |Cite
|
Sign up to set email alerts
|

Superior supercapacitive performance in electrospun copper oxide nanowire electrodes

Abstract: Electrospun CuO nanowires from an aqueous polymeric solution gave the highest specific capacitance so far achieved in this material when tested as a supercapacitor electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
94
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(98 citation statements)
references
References 55 publications
0
94
1
Order By: Relevance
“…Electrochemical reversibility, availability of an array of oxidation states and higher electrical conductivity are the properties of a material to be selected as a pseudocapacitor electrode. Many transition metal oxides (TMOs) are proposed as candidates for pseudocapacitive electrodes; summary of which are available in recent articles [5][6][7][8][9][10][11][12][13][14]. Among them, compounds of cobalt offer superior performance than other binary metal oxides although they are expensive due to its lower abundance in the earth's crust (<10 ppm).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical reversibility, availability of an array of oxidation states and higher electrical conductivity are the properties of a material to be selected as a pseudocapacitor electrode. Many transition metal oxides (TMOs) are proposed as candidates for pseudocapacitive electrodes; summary of which are available in recent articles [5][6][7][8][9][10][11][12][13][14]. Among them, compounds of cobalt offer superior performance than other binary metal oxides although they are expensive due to its lower abundance in the earth's crust (<10 ppm).…”
Section: Introductionmentioning
confidence: 99%
“…So far, electrode materials can be classified as metal oxides, polymers, and carbon-based composites [15][16][17]. Metal oxides and composites such as NiO, CoO, Co 3 O 4 /Ni(OH) 2 , MnO 2 , CuO, and CoS 2 exhibit higher specific capacitance than carbon and polymer materials [18][19][20][21][22][23][24] Experimental section Material preparation Figure 1 presents the hydrothermal fabrication process of the NiMn 2 O 4 nanosheets. In a typical synthesis, 0.582 g Ni(NO 3 ) 2 · 6H 2 O (purity 99.9 %, Sigma-Aldrich, USA), 0.965 g MnCl 2 · 4H 2 O (purity 99.9 %, Sigma-Aldrich, USA), and 0.4 g urea (AR, China) were stirred in a mixture of 5 mL ethanol and 35 mL deionized water for 30 min to obtain a clear solution.…”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, these nanostructures can be easily converted to CuO 20,22,23 which is known as a p-type semiconductor with a narrow indirect bandgap of 1.2-1.5 eV at room temperature (RT), 24,25 with variety of applications in sensors, solar cells, Li-ion battery electrodes 26,27 and supercapacitors. [28][29][30][31][32] CuO as a supercapacitor electrode has speci¯c capacitance in the range of 100-620 F/g. 30,32 The recent studies have shown that metal hydroxides materials are prone to deliver better capacitance than metal oxides due to higher stability especially in alkaline solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] CuO as a supercapacitor electrode has speci¯c capacitance in the range of 100-620 F/g. 30,32 The recent studies have shown that metal hydroxides materials are prone to deliver better capacitance than metal oxides due to higher stability especially in alkaline solutions. 33,34 It has been reported that grain size and morphology of the electrode materials considerably a®ect the speci¯c capacity of supercapacitors.…”
Section: Introductionmentioning
confidence: 99%